Moedig in de Marge: Leidse revolutionair-socialisten tussen de wereldoorlogen als politieke familie - van der Steen, Bart; Andrée, Aela; Helmus, Merle (TSEG - The Low Countries Journal of Social and Economic History, 2024)
This paper reconstructs the history of revolutionary socialists in the city of Leiden during the interbellum in order to test the efficacy of the concept of ‘political family’ for analyzing historical political cultures. The revolutionary socialist movement split from the official communist movement in the late 1920s and was active throughout the 1930s. It was critical of Stalin, sympathized with Trotsky and supported the radical trade union Nationaal Arbeids-Secretariaat. Historians have approached the revolutionary socialist movement as a moral community, revealing how its politics provided meaning and informed certain ways of life, cultural production and social interactions. The more recent concept of political family has a local focus and emphasizes how social networks influence local party dynamics. After analyzing the rise, flourishing and decline of the Leiden revolutionary movement in the 1920s and 1930s, this paper argues that while the term ‘moral community’ enables analyses of general party cultures, the concept of ‘political family’ is essential for understanding how these party cultures developed in local settings. The case study show that the terms are not only compatible, but build on and strengthen each other.